PROBLEMS IMPLEMENTING INCLUSIVE EDUCATION POLICY AT TRI MURTI ELEMENTARY SCHOOL DENPASAR - Ari, Ida Ayu Nyoman Maye Denia; Lasmawan, I Wayan; Suharta, I Gusti Putu (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
Inclusive education is a policy implemented to integrate students with disabilities into the general education system. However, its implementation in the field still faces various obstacles. SD Tri Murti Denpasar, as one of the schools implementing this policy, has begun integrating students with disabilities since 2021. This research uses qualitative methods with a case study approach. Data sources were obtained through interviews, observation and documentation. The research subjects were teachers, school principals, and students' parents. The problems faced by Tri Murti Elementary School in implementing inclusive education include a lack of teacher readiness to teach students with disabilities, a lack of infrastructure to support inclusive learning, an increasing workload on teachers, and a lack of support from parents and the local community. The conclusion of the research is that a teacher competency development program is needed, provision of supporting facilities, alliance with parents and the community, as well as ongoing evaluation of the process of implementing inclusive education policies in schools.